2021
DOI: 10.1136/bmjdrc-2021-002299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of COVID-19-related severity in people with type 2 diabetes

Abstract: IntroductionPeople with type 2 diabetes (T2D) have an increased rate of hospitalization and mortality related to COVID-19. To identify ahead of time those who are at risk of developing severe diseases and potentially in need of intensive care, we investigated the independent associations between longitudinal glycated hemoglobin (HbA1c), the impact of common medications (metformin, insulin, ACE inhibitors (ACEIs), angiotensin receptor blockers (ARBs), and corticosteroids) and COVID-19 severity in people with T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Coronaviruses, which are human pathogens, interact with target cells via the angiotensin-converting enzyme whose expression may be increased in diabetics' epithelial cells and intestines, kidneys, and blood vessels[ 10 ]. COVID-19 infection and subsequent development of severe disease have been associated with individuals with T2D[ 31 , 32 ]. There is evidence that COVID-19 may increase the risk of hospitalization and mortality in individuals with T2D[ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronaviruses, which are human pathogens, interact with target cells via the angiotensin-converting enzyme whose expression may be increased in diabetics' epithelial cells and intestines, kidneys, and blood vessels[ 10 ]. COVID-19 infection and subsequent development of severe disease have been associated with individuals with T2D[ 31 , 32 ]. There is evidence that COVID-19 may increase the risk of hospitalization and mortality in individuals with T2D[ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 infection and subsequent development of severe disease have been associated with individuals with T2D[ 31 , 32 ]. There is evidence that COVID-19 may increase the risk of hospitalization and mortality in individuals with T2D[ 31 , 33 ]. It has been determined that T2D is a sole risk factor for COVID-19 severity[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Registry studies have identified hyperglycaemia at admission as a significant, independent predictor of Covid-19 hospitalisation or mortality ( O'Malley et al, 2021 ; Carrasco-Sánchez et al, 2021 ). The severity of hyperglycaemia appears to influence prognosis, appreciating that blood glucose can rise quickly during Covid-19 infection as seen with plasma glucose measurements but not with the gradual effect on HbA1c ( Zhang Q. et al, 2020 ; Wang B. et al, 2021 ; Ling et al, 2021 ). Hyperglycaemia is associated with adverse Covid-19 outcomes whether or not patients have diabetes ( Cai et al, 2020 ; Carrasco-Sánchez et al, 2021 ), with some suggestion of a more severe effect on Covid-19 prognosis for newly-diagnosed versus pre-existing diabetes, possibly associated with depressed respiratory function ( Aggarwal et al, 2020 ; Fadini et al, 2020 ).…”
Section: Diabetes and Covid-19 Outcomesmentioning
confidence: 99%
“…In the diabetic state, the RAS is activated in the pancreas, and angiotensin II (AngII), downstream of the RAS, is strongly associated with islet dysfunction in experimental models. Angiotensin-converting enzyme 2 (ACE2) promotes the degradation of AngII into angiotensin (1)(2)(3)(4)(5)(6)(7) [Ang(1-7)] (8,9), and Ang(1-7) acts through the G protein-coupled receptor Mas and opposes many of the actions of AngII (28,29). The ACE2/Ang(1-7)/Mas axis serves as a protective and negative regulator of RAS (30).…”
Section: New-onset Diabetes In Covid-19 Patientsmentioning
confidence: 99%
“…Based on the reports thus far, diabetes does not appear to increase the risk of contracting SARS-CoV; however, when infected, the risk of hospitalization, intensive care unit (ICU) admission, and mortality increase (2,3). When patients with diabetes are managed with good glycemic control for a long period, the risk of developing severe COVID-19 is reduced (4).…”
Section: Introductionmentioning
confidence: 99%